(untitled) (Journal of Contemporary Studies, 2012)
Abstract Afghanistan, a crossroads of civilizations has been a victim of global conspiracies for centuries. In recent history, the Soviet invasion (1979 to1989) and the subsequent covert U.S. campaign to disintegrate the former, has deeply influenced the social, political and economic sphere of Afghanistan, as well as neighboring Pakistan. The Soviet withdrawal in 1989, followed by the hasty U.S. departure, encouraged factional fighting and gave rise to a civil war like situation in the country. The situation paved way for the extremist Taliban government that could attain neither domestic public acceptance nor the recognition of the international community. The country was further destabilized by undesired U.S. invasion of Afghanistan in the wake of 9/11 attacks. Despite the military invasion, the U.S. found itself unable to subdue the opposition groups in Afghanistan. A decade into the invasion, the Taliban have grown stronger and more effective, and have emerged as a challenge for both the Afghan administration and the International Security Assistance Force (ISAF). Contrary to its claims, the United States has failed to curb militants. Foreseeing a troubled future, it has finally decided to negotiate with the Taliban for either an honourable exit or peaceful co-existence. The idea of this political engagement of the Taliban began a few years ago and U.S. representatives commenced negotiations with the Taliban at their newly established contact point in Doha, Qatar, at the beginning of 2012. Subsequently, the Afghan President Hamid Karzai invited the Taliban for direct talks. The wartorn people of Afghanistan need stability and peace in whatever form they can attain. However, for a durable